2011
DOI: 10.1111/j.1758-2229.2010.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Spiroplasma as a model insect endosymbiont

Abstract: Members of the genus Spiroplasma are actively motile and helical bacteria of the class Mollicutes, which are associated with a variety of arthropods and plants. Some spiroplasmas cause female-biased sex ratios of their host insects as a result of selective death of the male offspring during embryogenesis. Several strains of male-killing spiroplasmas have been successfully transfected into Drosophila melanogaster by haemolymph injection and maintained in laboratory fly stocks. Spiroplasma-Drosophila endosymbios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 86 publications
0
63
0
Order By: Relevance
“…2006). These features, together with the feasibility of using Drosophila as a host, make Spiroplasma a promising system for investigating the molecular mechanisms of insect–symbiont interactions (Haselkorn, Markow and Moran 2009; Anbutsu and Fukatsu 2011; Herren et al. 2013; Harumoto, Anbutsu and Fukatsu 2014).…”
Section: Recent Progress In Facultative Insect Symbiontsmentioning
confidence: 99%
“…2006). These features, together with the feasibility of using Drosophila as a host, make Spiroplasma a promising system for investigating the molecular mechanisms of insect–symbiont interactions (Haselkorn, Markow and Moran 2009; Anbutsu and Fukatsu 2011; Herren et al. 2013; Harumoto, Anbutsu and Fukatsu 2014).…”
Section: Recent Progress In Facultative Insect Symbiontsmentioning
confidence: 99%
“…or mutualistic (22). Maternal transmission has arisen numerous times in Spiroplasma, including strains that are well known as male-killers (22).…”
Section: Significancementioning
confidence: 99%
“…Maternal transmission has arisen numerous times in Spiroplasma, including strains that are well known as male-killers (22). In addition to defense against nematodes in D. neotestacea, other strains of Spiroplasma have recently been shown to protect flies and aphids against parasitic wasps and pathogenic fungi, respectively (23)(24)(25), but in no case is the mechanism of defense understood.…”
Section: Significancementioning
confidence: 99%
“…A third study confirmed the dominance of Tenericutes (36.6%), Proteobacteria (34.1%), and Firmicutes (26.2%), and at the genus level also Spiroplasma (38.7%) [53]. Members of the genus Spiroplasma are small, helical, motile and wall-less bacteria [54]. These species promote male-killing to yield extreme female-biased sex ratios in insects and can also cause diseases in mammals, including humans [55][56][57][58].…”
Section: Microbial Contaminationmentioning
confidence: 80%